2020
DOI: 10.1186/s12870-020-02499-w
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic diversity of SAD and FAD genes responsible for the fatty acid composition in flax cultivars and lines

Abstract: Background Flax (Linum usitatissimum L.) is grown for fiber and seed in many countries. Flax cultivars differ in the oil composition and, depending on the ratio of fatty acids, are used in pharmaceutical, food, or paint industries. It is known that genes of SAD (stearoyl-ACP desaturase) and FAD (fatty acid desaturase) families play a key role in the synthesis of fatty acids, and some alleles of these genes are associated with a certain composition of flax oil. However, data on genetic polymorphism of these gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 30 publications
1
37
1
Order By: Relevance
“…The expression of FAD2A was higher in capsules and embryo than in other analyzed tissues, and clustering had some concordance with flax type, but it was poor enough (Supplementary Figure S4m). It is known that FAD2 catalyzes the desaturation of oleic acid into linoleic acid, while FAD3 catalyzes linoleic acid into linolenic acid, and polymorphisms of FAD genes are associated with the content of these fatty acids, which was especially clearly shown for FAD3A and FAD3B genes [34,71,[103][104][105]. However, the present study did not reveal an association between flax type and polymorphisms in FAD3A and FAD3B genes.…”
Section: Genes Involved In Fatty Acid Synthesiscontrasting
confidence: 80%
“…The expression of FAD2A was higher in capsules and embryo than in other analyzed tissues, and clustering had some concordance with flax type, but it was poor enough (Supplementary Figure S4m). It is known that FAD2 catalyzes the desaturation of oleic acid into linoleic acid, while FAD3 catalyzes linoleic acid into linolenic acid, and polymorphisms of FAD genes are associated with the content of these fatty acids, which was especially clearly shown for FAD3A and FAD3B genes [34,71,[103][104][105]. However, the present study did not reveal an association between flax type and polymorphisms in FAD3A and FAD3B genes.…”
Section: Genes Involved In Fatty Acid Synthesiscontrasting
confidence: 80%
“…Over 70% of ASO constitutes unsaturated FAs, and FAD is a key enzyme in their synthesis [ 32 , 33 ]. In this study, we identified four FAD genes, including two SAD and two FAD2 genes.…”
Section: Resultsmentioning
confidence: 99%
“…One microgram of RNA for each sample was treated with DNase I (Thermo Fisher Scientific, Waltham, MA, United States) and used for reverse transcription with random hexamer primers (Evrogen, Moscow, Russia) and Mint reverse transcriptase (Evrogen) following the manufacturer's protocol. Primers were designed for amplification of parts of the TCP, CLC, and MET1 genes and further sequencing on the Illumina platform as described in our previous works (Melnikova et al, 2019;Dmitriev et al, 2020;Novakovskiy et al, 2020). In brief, two PCRs were used for the library preparation.…”
Section: Targeted Genome and Transcriptome Sequencingmentioning
confidence: 99%